Miniaturized low-profile filtering omnidirectional antenna design - Wang Lili; Xu Yani; Gao Zhiyong; Zhang Heng (Dianzi Jishu Yingyong)
A miniaturized omnidirectional microstrip filter antenna is designed. The antenna is composed of a bandpass filter and a microstrip antenna, which share a ground plane to reduce the size and are connected by gap coupling. The bandpass filter is etched at the feeder position of the microstrip patch antenna, and the frequency selection filter function is introduced. A transverse rectangular patch is added at the front end of the input feeder to achieve good impedance matching of the whole system. Compared with the traditional microstrip antenna, the designed filter antenna introduces the frequency selection filter function without changing the size, and shows high selectivity at the edge of the passband. The simulation and test results show that the impedance bandwidth of the filter antenna is 2.31 GHz~2.56 GHz, and the gain in the passband is flat, the average gain is about 2.1 dBi, and the filter antenna has omnidirectional radiation characteristics in the working frequency band.